Asynchronous stabilization of switched neutral systems: A cooperative stabilizing approach. (August 2019) - Liu, Guopin; Hua, Changchun; Guan, Xinping
Abstract: This paper considers the stabilization problem for a class of switched neutral systems under asynchronous switching. A cooperative stabilization approach is presented, which means that controllers and switching signals are designed cooperatively to stabilize the switched system. Based on the Lyapunov–Krasovskii functional approach, a sufficient condition is provided to guarantee the global asymptotical stability of the switched neutral systems. Meanwhile, the controller gain is obtained by solving the established linear matrix inequalities (LMIs). The proposed approach allows the Lyapunov-like function to increase not only at the running time in mode-identifying process but also in normal-working period with matched controller. Thus, switched systems, which contain unstable and uncontrollable subsystems, can be stabilized by the proposed scheme. A numerical example further demonstrates the validity of the developed results.